Poétipo: instabilidade e sentido do elemento tipográfico na obra de Arlindo Daibert - Leticia Christiane Guimaraes de Senna (2012)
Interested in the interplay of text and image, we revisited in this researchthe work of the brazilian artist Arlindo Daibert, aiming at observing a mainaspect of his poetics: the use of the typographic element on works of plastics art. Based on Gérard Genettes theory of the imanence regimes of the artwork, we propose an adaptation on the tipology table, presented by Bernard Vouilloux, for the classification of the interplay between text and image, in order to show that, not only is there a development on the use of typographic elements in Daiberts work, but also that such development constitutes the process of destabilization of meaning, that with this paper we popose to call poétipo.